Republic of Poland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues papers review factors that drive wage growth in Poland and studies structural characteristics and firm-level total factor productivity (TFP) in Poland and Emerging Europe. The increase in real unit labor costs (RULC) occurred alongside an unprecedently tight labor market. The study highlights that the more subdued RULC dynamics compared with the pre-crisis period, despite the now-lower unemployment rate, may reflect the recent influx of foreign workers. In order to more systematically identify the long- and short-term drivers of Polish wages, an Error-correction model has been used. Analyses presented in the paper using both Statistics Poland and Orbis data show that foreign-owned firms are associated with strong TFP performance through above-average TFP levels and growth rates. The findings suggest the need to create an environment conducive to entrepreneurship by reducing barriers to entry and ensuring a level playing field between state owned and private firms, while also avoiding barriers to scaling up businesses while encouraging investments in innovation and research and development.